Mitoferrin-1 is required for brain energy metabolism and hippocampus-dependent memory. (20th November 2019) - Baldauf, Lisa; Endres, Thomas; Scholz, Johannes; Kirches, Elmar; Ward, Diane M.; Lessmann, Volkmar; Borucki, Katrin; Mawrin, Christian
Highlights: First-time generation of a neuron-specific mitoferrin-1 knockout mouse. Knockout animals had no neuropathology and had normal life span. Brain tissue from these mice exhibited decreased brain mitochondrial O2 -consumption with complex-I substrates of the ETC. Knockout mice had impaired spatial learning capacity. Abstract: Disturbed iron (Fe) ion homeostasis and mitochondrial dysfunction have been implicated in neurodegeneration. Both processes are related, because central Fe ion consuming biogenetic pathways take place in mitochondria and affect their oxidative energy metabolism. Iron is imported into mitochondria by the two homologous Fe ion importers mitoferrin-1 and mitoferrin-2. To elucidate more specifically the role of mitochondrial Fe ions for brain energy metabolism and for proper neuronal function, we generated mice with a neuron-specific knockout of mitoferrin-1 ( Slc25a37 −/− or mfrn-1 −/− ) and compared them with corresponding control littermates ( mfrn-1 flox/flox ). Mice lacking neuronal mfrn-1 exhibited no obvious anatomical or behavioral abnormalities as neonates, young or adult animals. However, they exhibited a moderate decrease in brain mitochondrial O2 -consumption with complex-I substrates of the electron transport chain (p < 0.05), indicating a moderate suppression of electron transport. While these mice did not exhibit altered basal fear levels, inquisitiveness or motor skills in specific neurobiological test batteries, they clearly exhibited decreased spatial learning skills and missing establishment of stable spatial memory in Morris water maze, as compared to floxed controls (p < 0.05). We thus conclude that mitochondrial Fe ion supply is an important player in neuronal energy metabolism and proper brain function and that the carrier mitoferrin-1 cannot be completely replaced by mitoferrin-2 or other as yet unknown Fe ion carriers.